Qualitative Analysis and Antibacterial Activity of Pelargonium graveolenL’Herit - Saraswathi Jaggali; Prem Kumar; Venkatesh K; Chakrapani P; Arun Jyothi B; Amareshwari P; Sudhakar C; Roja Rani Anupalli (International Journal of Phytomedicine, 2016)
Medicinal plants are an important source of phytochemicals that offer traditional medicinal treatment of various ailments and one of the plants is Pelargonium Graveolens which was grown in Hyderabad province. The preliminary screening of their aerial leaves showed best results the presence of different phytochemical like alkaloids, flavonoids, glycosides, phenol, sterol and lignin found in Methanolic and Ethyl acetate extract. However chloroform extract revealed the absence of alkaloids and sterols, where as in Water extract flavonoids, phenol, sterol and lignin. The best resulted extracts from preliminary screening test were subjected to Antimicrobial studies like some on gram positive and gram negative bacterial strains which exhibited a significant effect. The both ethyl acetate and methanolic extracts were showed the similar zone of inhibition on gram positive bacteria (S.aurea and B.Subtilus) whereas ethyl acetate extract positive inhibition on k.pneumonia when compare to methanolic extract and which are more active suppression on gram negative bacterial (E.coli) in comparison with the standard antibiotic.